2016
DOI: 10.1371/journal.pone.0158362
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Bird Species and Feeding Guilds along Elevational Gradients of the Central Himalayas, Nepal

Abstract: The Himalayas are a global hotspot for bird diversity with a large number of threatened species, but little is known about seasonal changes in bird communities along elevational gradients in this region. We studied the seasonality of bird diversity in six valleys of the Central Himalayas, Nepal. Using 318 plots with a 50 m radius, located from 2200 to 3800 m a.s.l., and repeated sampling during different seasons (mainly pre-monsoon, monsoon, and post-monsoon), we analyzed 3642 occurrences of 178 species. Birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 63 publications
8
39
0
Order By: Relevance
“…From the point-count survey of two seasons (summer and winter), we recorded a total of 112 species of birds belonging to 13 orders and 35 families. We observed that insectivorous form is the most species-rich feeding guild in the Mardi Himal, which is consistent to many other studies in birds (Herzog et al 2005;De Bonilla et al 2012;Katuwal et al 2016). About 29% (32/112) of the bird species observed in Mardi Himal are migratory birds which is almost similar to the observation of Neupane et al (2020) along the Kaligandaki River basin of the ACA but lesser proportion than that of the overall contribution of migrants (38%, 336/884) (Grimmett et al 2016) in the avian diversity of Nepal.…”
Section: Avian Diversity In Mardi Himalsupporting
confidence: 93%
See 1 more Smart Citation
“…From the point-count survey of two seasons (summer and winter), we recorded a total of 112 species of birds belonging to 13 orders and 35 families. We observed that insectivorous form is the most species-rich feeding guild in the Mardi Himal, which is consistent to many other studies in birds (Herzog et al 2005;De Bonilla et al 2012;Katuwal et al 2016). About 29% (32/112) of the bird species observed in Mardi Himal are migratory birds which is almost similar to the observation of Neupane et al (2020) along the Kaligandaki River basin of the ACA but lesser proportion than that of the overall contribution of migrants (38%, 336/884) (Grimmett et al 2016) in the avian diversity of Nepal.…”
Section: Avian Diversity In Mardi Himalsupporting
confidence: 93%
“…2009; Voskamp et al 2017;Somveille et al 2018) as well as local spatial scales (Ruggiero and Hawkins 2008;Wu et al 2013;Katuwal et al 2016;Pan et al 2016). Avian species richness along the elevational gradient has been found to display four distinct patterns: decreasing richness, low-elevation plateaus, low-elevation plateaus with mid-peaks and mid-elevational peaks (McCain 2009).…”
mentioning
confidence: 99%
“…As previously well-documented, seasonality (Caula et al, 2008;Chen et al, 2019;Gomes et al, 2017;Girma et al, 2017;Katuwal et al, 2016) and habitat (Caula et al, 2008;Chen et al, 2018;Chen et al, 2019;Durmuş et al, 2018;Girma et al, 2017) influence the species richness and population size. The present results of the study are consistent with the previous reports given above.…”
Section: Fig 2 Bird Population Density Graph On Akdoğan Lakementioning
confidence: 72%
“…; Katuwal et al . ), we obtained information from the Handbook of Australian, New Zealand and Antarctic Birds (HANZAB) (Marchant & Higgins , ; Higgins & Davies ; Higgins ; Higgins et al . , ; Higgins & Peter ) on feeding guild and body size for each bird species.…”
Section: Methodsmentioning
confidence: 99%
“…; Katuwal et al . ). Associating species traits and environmental variables using species abundance data is a challenge in multivariate ecological analysis known as the fourth‐corner problem.…”
Section: Introductionmentioning
confidence: 97%